Strukturasi dan Penguatan Ketahanan Desa: Tinjauan Hukum Atas Implementasi Sistem Pemerintahan Desa Berbasis Elektronik - Airlangga Surya Nagara; Reza Ilham Maulana (Jurnal Pembangunan Hukum Indonesia, 2025)
The modernization of village governance holds significant potential to enhance efficiency, transparency, and active community participation through Presidential Regulation No. 95 of 2018 and Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration No. 22 of 2019. However, its implementation faces challenges due to resistance rooted in social and cultural norms. This study aims to strengthen the structural resilience of villages through a socio-legal positivist approach, with a primary focus on reinforcing the legal system.The method employed in this research is a socio-legal approach using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) analysis technique. The findings reveal that technological changes in governance systems influence the structural relationship between agency and structure. The implementation of e-government as a means to enhance village resilience can be achieved through clarity in both structural and legal frameworks, utilizing socio-legal positivist analysis to address issues of social, cultural, and legal policy disparities.The conclusion drawn from this study indicates that village resilience can be reinforced through e-government, which depends on the readiness of social infrastructure and legal comprehension that reflects the local community’s cultural values.